Heart rate variability dynamics in women with urinary incontinence: a systematic review - Silva, Jordana Barbosa da; Abreu, Raphael Martins de; Padilha, Juliana Falcão; Silva, Audrey Borghi; Catai, Aparecida Maria; Driusso, Patricia (Universidade Federal de São Carlos, 2022)
Introduction and hypothesis Sympathetic and parasympathetic pathways of the autonomic nervous system (ANS) regulate the lower urinary tract. The aim of the present study was to synthesize the evidence regarding ANS regulation in women with urinary incontinence (UI) evaluated through heart rate variability (HRV). Methods This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Five databases were researched in April 2021 (PubMed, CINHAL, Scopus, Web of Science and Cochrane Library) and included cross-sectional studies in full-length publications in the English language. Studies assessed the HRV during bladder filling (group A) and after voiding (group B). The Joanna Briggs Institute (JBI) checklist was applied for methodological quality assessment purposes. Results A total of 920 articles were identified and 5 studies were included. Most studies analyzed the HRV by linear indexes. Studies from group A (n = 2) presented fair methodological quality; one study from group B (n = 3) showed fair methodological quality (Im et al. Korean J Urol. 51:183, 2010) whereas the others presented high methodological quality. One study from group A found an increase in both modulations between women with overactive bladder (OAB) versus women with stress UI, whereas a decrease was reported between incontinent and continent women. Studies from group B showed a decreased sympathetic and parasympathetic modulation in AOB with detrusor overactivity (DO), whereas one study found an increase in both modulations in women with OAB compared with stress UI. Conclusion Parasympathetic and sympathetic modulation increased during bladder filling and rest in UI with OAB associated or not with DO. Both modulations decreased during bladder filling in incontinent women and during rest in OAB.
Keywords: Cardiovascular system; Women’s health; Urinary incontinence; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::GINECOLOGIA E OBSTETRICIA